2017
DOI: 10.1259/bjr.20170115
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and chemical forms of gadolinium in the brain: a review

Abstract: In the 3 years since residual gadolinium-based contrast agent (GBCA) in the brain was first reported, much has been learned about its accumulation, including the pathway of GBCA entry into the brain, the brain distribution of GBCA and its excretion. Here we review recent progress in understanding the routes of gadolinium deposition in brain structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 52 publications
2
32
0
1
Order By: Relevance
“…Gadolinium accumulation in the brain after multiple intravenous administrations has been a major concern since it was first reported in 2014 (61). However, there have been no reports demonstrating brain toxicity (62); the US Food and Drug Administration and American College of Radiology have declared that there is no evidence to date that gadolinium accumulation in the brain is harmful and that there is no need to restrict its intravenous usage. In the present study, where intrathecal administration of an MRI contrast agent was utilized, no serious adverse events were noted among our study subjects, and at the 4-week MRI follow-up, no evidence of remaining gadobutrol within brain parenchyma or CSF was found (Supplemental Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gadolinium accumulation in the brain after multiple intravenous administrations has been a major concern since it was first reported in 2014 (61). However, there have been no reports demonstrating brain toxicity (62); the US Food and Drug Administration and American College of Radiology have declared that there is no evidence to date that gadolinium accumulation in the brain is harmful and that there is no need to restrict its intravenous usage. In the present study, where intrathecal administration of an MRI contrast agent was utilized, no serious adverse events were noted among our study subjects, and at the 4-week MRI follow-up, no evidence of remaining gadobutrol within brain parenchyma or CSF was found (Supplemental Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, where intrathecal administration of an MRI contrast agent was utilized, no serious adverse events were noted among our study subjects, and at the 4-week MRI follow-up, no evidence of remaining gadobutrol within brain parenchyma or CSF was found (Supplemental Table 5). Interestingly, gadolinium deposits in brain tissue have recently been attributed to leakage from blood into CSF through the choroid plexus and entrance into the brain from the surface along perivascular spaces (62). In rats, gadolinium concentration has been shown to be higher in CSF than blood 4.5 hours after intravenous distribution and highest in brain after 24 hours (63).…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, some concern has been raised on the use of intravenous contrast (gadolinium-chelates) given the potential accumulation in basal ganglia of the brain. [28][29][30] However, the use of gadolinium contrast products is part of the routine practice in most institutions and currently recommended in clinical guidelines. 31 The MARIAs can be obtained without the use of gadolinium contrast agents, as the degree of enhancement is not part of the new simplified index.…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy studies have shown that gadolinium deposition in the posterior fossa and basal ganglia is not limited to patients with intracranial abnormalities but can also be detected in patients with normal brains at the time of autopsy [17,18]. Several mechanisms of this gadolinium transit and retention in brain regions without impaired BBB have been suggested including active metal transporters [19,20], passage from the cerebrospinal fluid [21][22][23], and brain glymphatic system [24]. The exact mechanism behind the retention, however, remains unsolved.…”
Section: Discussionmentioning
confidence: 99%